2020
DOI: 10.1017/s0960258520000203
|View full text |Cite
|
Sign up to set email alerts
|

Epicotyl morphophysiological dormancy and storage behaviour of seeds of Strychnos nux-vomica, Strychnos potatorum and Strychnos benthamii (Loganiaceae)

Abstract: Abstract We hypothesized that Strychnos nux-vomica and Strychnos potatorum in seasonal tropical ecosystems have dormant desiccation-tolerant seeds, while those of Strychnos benthamii growing in aseasonal wet habitats have non-dormant desiccation-sensitive seeds. Germination, imbibition, the effect of gibberellic acid on germination and changes in the embryo to seed length ratio (E:S) during incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Fourteen of the study species have been previously studied and dormancy classes were identified or speculated. Six of the above 14 species have previously been studied in different ecosystems [Urophyllum ceylanicum, Turpinia malabarica, Bhesa nitidissima and Eurya ceylanica in tropical mountain forests (Athugala et al, 2021), and Messua ferrea (Troup, 1921;Joshi et al, 2015) and Dillenia indica (Thapliyal et al, 2008) in tropical semi-evergreen forests], while the rest of the species (eight) have been studied in the same ecosystem [Mangifera zeylanica and Dipterocarpus zeylanicus (Holmes, 1954), Shorea affinis (Tompsett, 1998) S. trapezifolia (de Zoysa, 1986) Strychnos benthamii (Muthuthanthirige et al, 2020) Humboldtia laurifolia (Jayasuriya et al, 2010), Gomphia serrata (Ng, 1992) and P. mooniana (Jayasuriya et al, 2013)]. The previously reported dormancy class (PD) of Bheasa nitidissima, Eurya ceylanica and Gomphia serrata are identified as ND in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen of the study species have been previously studied and dormancy classes were identified or speculated. Six of the above 14 species have previously been studied in different ecosystems [Urophyllum ceylanicum, Turpinia malabarica, Bhesa nitidissima and Eurya ceylanica in tropical mountain forests (Athugala et al, 2021), and Messua ferrea (Troup, 1921;Joshi et al, 2015) and Dillenia indica (Thapliyal et al, 2008) in tropical semi-evergreen forests], while the rest of the species (eight) have been studied in the same ecosystem [Mangifera zeylanica and Dipterocarpus zeylanicus (Holmes, 1954), Shorea affinis (Tompsett, 1998) S. trapezifolia (de Zoysa, 1986) Strychnos benthamii (Muthuthanthirige et al, 2020) Humboldtia laurifolia (Jayasuriya et al, 2010), Gomphia serrata (Ng, 1992) and P. mooniana (Jayasuriya et al, 2013)]. The previously reported dormancy class (PD) of Bheasa nitidissima, Eurya ceylanica and Gomphia serrata are identified as ND in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We may, however, expect other relationships in less seasonal tropical areas, for which very little is known (with some exceptions, e.g. Muthuthanthirige et al , 2020 ). For example, a strong positive relationship has been observed for relative embryo size and seed size ( Vandelook et al , 2012 ).…”
Section: Case Example 2: Bias Of Relative Embryo Size and Post-disper...mentioning
confidence: 99%